2015
DOI: 10.1039/c5ra03262h
|View full text |Cite
|
Sign up to set email alerts
|

Linseed oil polyol/ZnO bionanocomposite towards mechanically robust, thermally stable, hydrophobic coatings: a novel synergistic approach utilising a sustainable resource

Abstract: Linseed oil polyol/ZnO bionanocomposite was prepared to obtain mechanically robust, thermally stable, hydrophobic coatings via a novel synergistic approach utilising a vegetable oil polyol for the first time.The synthesis process obviates the use of reducing agents, surfactants, reaction media, stabilizing agents, solvents, and other chemicals. Linseed polyol serves the purpose of obtaining ZnO nanoparticles. The linseed polyol backbone hosts hydroxyl and carboxylic groups that participate in the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…6 Functionalization of plant oils by epoxidation, transesterification, ozonolysis, and radical additions for the use in PU synthesis has been reported in various researches. [6][7][8][9][10][11][12][13][14][15][16][17] Thiol-ene click chemistry is a facile and efficient method for the synthesis of multifunctional materials. [18][19][20][21] Due to its simple reaction conditions, stereoselectivity, high rate and high yield, thiol-ene reactions have attracted the attention of many researches for the utilization of plant oils as feedstock for biopolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Functionalization of plant oils by epoxidation, transesterification, ozonolysis, and radical additions for the use in PU synthesis has been reported in various researches. [6][7][8][9][10][11][12][13][14][15][16][17] Thiol-ene click chemistry is a facile and efficient method for the synthesis of multifunctional materials. [18][19][20][21] Due to its simple reaction conditions, stereoselectivity, high rate and high yield, thiol-ene reactions have attracted the attention of many researches for the utilization of plant oils as feedstock for biopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…To utilize plant oils without any inherent functional group, hydroxyl functional groups need to be introduced to its unsaturated reactive sites . Functionalization of plant oils by epoxidation, transesterification, ozonolysis, and radical additions for the use in PU synthesis has been reported in various researches …”
Section: Introductionmentioning
confidence: 99%
“…LO is one of the most popular NEVOs to be used in polymer field. Reports have been published on the development of different types of polyols from LO and their applications in polyester/PU coatings [ 38 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Nonedible Vegetable Oils For Polyolsmentioning
confidence: 99%
“…The results of investigating the scratch resistance of the prepared polyurethane coatings revealed that increased content of ternary nanocomposite would lead to improved scratch resistance of the coatings. This improvement results from the interactions between ZnO nanoparticle and polyurethane chains which compact the polyurethane chains and increase their resistance against tearing [32].…”
Section: Evaluation Of the Coatings' Adhesion Strength And Scratch Rementioning
confidence: 99%